Long-acting cabotegravir and rilpivirine dosed every 2 months in adults with HIV-1 infection (ATLAS-2M), 48-week results: a randomised, multicentre, open-label, phase 3b, non-inferiority study. Issue 10267 (19th December 2020) - Overton, Edgar T; Richmond, Gary; Rizzardini, Giuliano; Jaeger, Hans; Orrell, Catherine; Nagimova, Firaya; Bredeek, Fritz; García Deltoro, Miguel; Swindells, Susan; Andrade-Villanueva, Jaime Federico; Wong, Alexander; Khuong-Josses, Marie-Aude; et al.
Summary: Background: Phase 3 clinical studies showed non-inferiority of long-acting intramuscular cabotegravir and rilpivirine dosed every 4 weeks to oral antiretroviral therapy. Important phase 2 results of every 8 weeks dosing, and supportive modelling, underpin further evaluation of every 8 weeks dosing in this trial, which has the potential to offer greater convenience. Our objective was to compare the week 48 antiviral efficacy of cabotegravir plus rilpivirine long-acting dosed every 8 weeks with that of every 4 weeks dosing. Methods: ATLAS-2M is an ongoing, randomised, multicentre (13 countries; Australia, Argentina, Canada, France, Germany, Italy, Mexico, Russia, South Africa, South Korea, Spain, Sweden, and the USA), open-label, phase 3b, non-inferiority study of cabotegravir plus rilpivirine long-acting maintenance therapy administered intramuscularly every 8 weeks (cabotegravir 600 mg plus rilpivirine 900 mg) or every 4 weeks (cabotegravir 400 mg plus rilpivirine 600 mg) to treatment-experienced adults living with HIV-1. Eligible newly recruited individuals must have received an uninterrupted first or second oral standard-of-care regimen for at least 6 months without virological failure and be aged 18 years or older. Eligible participants from the ATLAS trial, from both the oral standard-of-care and long-acting groups, must have completed the 52-week comparative phase with an ATLAS-2M screening plasma HIV-1 RNA less than 50 copies per mL. Participants were randomly assigned 1:1 to receive cabotegravir plus rilpivirine long-acting every 8 weeks or every 4 weeks. The randomisation schedule was generated by means of the GlaxoSmithKline validated randomisation software RANDALL NG. The primary endpoint at week 48 was HIV-1 RNA ≥50 copies per mL (Snapshot, intention-to-treat exposed), with a non-inferiority margin of 4%. The trial is registered at ClinicalTrials.gov, NCT03299049 and is ongoing. Findings: Screening occurred between Oct 27, 2017, and May 31, 2018. Of 1149 individuals screened, 1045 participants were randomised to the every 8 weeks (n=522) or every 4 weeks (n=523) groups; 37% (n=391) transitioned from every 4 weeks cabotegravir plus rilpivirine long-acting in ATLAS. Median participant age was 42 years (IQR 34–50); 27% (n=280) female at birth; 73% (n=763) white race. Cabotegravir plus rilpivirine long-acting every 8 weeks was non-inferior to dosing every 4 weeks (HIV-1 RNA ≥50 copies per mL; 2% vs 1%) with an adjusted treatment difference of 0·8 (95% CI −0·6–2·2). There were eight (2%, every 8 weeks group) and two (<1%, every 4 weeks group) confirmed virological failures (two sequential measures ≥200 copies per mL). For the every 8 weeks group, five (63%) of eight had archived non-nucleoside reverse transcriptase inhibitor resistance-associated mutations to rilpivirine at baseline. The safety profile was similar between dosing groups, with 844 (81%) of 1045 participants having adverse events (excluding injection site reactions); no treatment-related deaths occurred. Interpretation: The efficacy and safety profiles of dosing every 8 weeks and dosing every 4 weeks were similar. These results support the use of cabotegravir plus rilpivirine long-acting administered every 2 months as a therapeutic option for people living with HIV-1. Funding: ViiV Healthcare and Janssen.